Perspective on Institutional Legitimacyof Sea-ranching at Seribu Island-Jakarta - ., Taryono; Soewardi, Kadarwan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTThe main problem of shallow water fisheries is overfishing. To improve fishing capacity of overfished fisheries is potentially by implementing sea ranching. Sea ranching isa process of releasing juvenile to certain enclose marine water under process of put-grow-take system. Two crucial aspects for implementing sea-ranching system are space management and access control of fishermen to fisheries resources. Implementation of this concept needsstrong legitimated institution. This paper is aimed to analysis legitimation issues of sea ranching institution at Semak Daun shallow water in Seribu Island-Jakarta base on legitimacy theory both of legal-substantial and sociopolitic-cognitive perspective.Legitimacy is heavily perception matter, which is assumed that institution body is allowed to take expected, proper and right actions. The legitimated sea ranching institutionrequires a powerful authority to develop regulations and to take enforcement actions. For doing so, itmust meet political, regulative, scientific and morality reasons. For complementary that institution also needs to be supported by institutional pillars including regulative, normative and cognitive perspectives. Results of this analysis will be one of references to develop implementing institution of sea ranching at study site.Keywords: institutional legitimacy, overfishing, sea-ranching, shallow waterABSTRAKProblem utama perikanan perairan dangkal adalah tangkap lebih.Untuk meningkatkan produktivtas perikanan yang tangkap lebih dapat dilakukan dengan menerapkan sea ranching. Sea ranching adalah pelepasan juvenil yang dibudidayakan ke lingkungan laut tertutup dalam sistem lepas-tumbuh-panen. Dua aspek krusial penerapansea-ranching adalah tata ruang dan pengendalian akses nelayan pada sumberdaya. Implementasi sea ranchingmemerlukan kelembagaan yang mempunyai legitimasi kuat. Artikel ini bertujuan untuk menganalisis isu-isu legitimasi kelembagaan sea ranching pada perairan dangkal Semak Daun di Kepulaun Seribu-Jakarta dalam pandangan teoritis baik dalam perspektif legal-substansial dan sosial politik-koginitif. Legitimasi lebih merupakan persoalan persepsi, yang diasumsikan bahwa lembaga diijinkan untuk melakukan suatu tindakan yang yang diharapkan, tepat dan benar. Lembaga pengelola sea ranching yang legitimatif membutuhkan kewenangan yang kuat untuk menyusun peraturan dan melakukan tindakan penegakannya. Untuk itu, kelembagaan sea ranching harus memenuhi alasan politis, regulatif, ilmiah, dan moralitas. Untuk melengkapinya, kelembagaan tersebut juga membutuhkan dukungan pilar-pilar kelembagaan yang mencakup perspektif regulatif, normatif dan kognitif.Hasil analisis ini dapat menjadi salah satu rujukan untuk membangun kelembagaan implementasi sea ranching di lokasi studi.Kata kunci: legitimasi kelembagaan, perairan dangkal, sea-ranching, tangkap lebih